the Teacher and Student Interaction in Improving Discipline Culture - Siska Handayani; Hamdani Abdi (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the interactions between teachers and students in building and enhancing a culture of discipline at Al-Istiqomah Senior High School, West Pasaman. Discipline in the school environment is a crucial aspect that supports the creation of a conducive learning environment, which in turn can maximize students' potential in both academics and character development. Teachers, as educators and role models, play a significant role in guiding students to comply with school regulations. This study used qualitative methods with a phenomenological approach to understand the dynamics of interactions between teachers and students in greater depth. Data were collected through observation, interviews with the principal, teachers, and students, and relevant school documentation. The results indicate that interaction patterns involving multi-directional communication between teachers and students are effective in strengthening a culture of discipline. Teachers not only provide instructions but also employ a persuasive and educational approach when reprimanding infractions. For example, students who are late are given educational punishments such as memorizing verses from the Quran, while more serious violations, such as smoking, are subject to mild physical sanctions, such as running. This approach not only enforces rules but also helps students understand the importance of discipline as part of character development. Consistent interactions between teachers and students also foster close and respectful relationships, thus making students more motivated to comply with rules. This research suggests that discipline in schools can be effectively improved through an approach that emphasizes positive interpersonal interactions and educational teaching methods. The practical implication of this research is that schools can design discipline programs that balance firmness and understanding, so that students understand not only the consequences but also the value of discipline itself.